A randomized, double‐blind, placebo‐controlled trial evaluating cysteamine in Huntington's disease. Issue 6 (24th April 2017) - Verny, Christophe; Bachoud‐Lévi, Anne‐Catherine; Durr, Alexandra; Goizet, Cyril; Azulay, Jean‐Philippe; Simonin, Clémence; Tranchant, Christine; Calvas, Fabienne; Krystkowiak, Pierre; Charles, Perrine; Youssov, Katia; Scherer, Clarisse; et al.
ABSTRACT: Background : Cysteamine has been demonstrated as potentially effective in numerous animal models of Huntington's disease. Methods : Ninety‐six patients with early‐stage Huntington's disease were randomized to 1200 mg delayed‐release cysteamine bitartrate or placebo daily for 18 months. The primary end point was the change from baseline in the UHDRS Total Motor Score. A linear mixed‐effects model for repeated measures was used to assess treatment effect, expressed as the least‐squares mean difference of cysteamine minus placebo, with negative values indicating less deterioration relative to placebo. Results : At 18 months, the treatment effect was not statistically significant — least‐squares mean difference, ‐1.5 ± 1.71 ( P  = 0.385) — although this did represent less mean deterioration from baseline for the treated group relative to placebo. Treatment with cysteamine was safe and well tolerated. Conclusions : Efficacy of cysteamine was not demonstrated in this study population of patients with Huntington's disease. Post hoc analyses indicate the need for definitive future studies. © 2017 International Parkinson and Movement Disorder Society